Targeting Endothelial Ligands: ICAM-1/alicaforsen, MAdCAM-1. (11th May 2018) - Reinisch, Walter; Hung, Kenneth; Hassan-Zahraee, Mina; Cataldi, Fabio
Abstract: Specific blockade of the endothelial ligands intercellular adhesion molecule-1 [ICAM-1] and mucosal addressin cell adhesion molecule [MAdCAM] involved in leukocyte recruitment to the site of inflammation as therapeutic targets in inflammatory bowel disease [IBD] has been recognized from their overexpression in the inflamed mucosa and successful intervention based on these ligands in preclinical animal models. Interventions to target ICAM-1 in human IBD are confined to the ICAM-1 anti-sense oligonucleotide alicaforsen. While results with parenteral formulations of alicaforsen in Crohn's disease have largely been negative, efficacy signals derived from studies with an enema formulation in ulcerative colitis and pouchitis are promising and have led to a Food and Drug Administration Fast-Track designation for the latter. A large phase III programme in pouchitis is underway. Phase II studies with the anti-MAdCAM-1 antibody [SHP647] delivered positive results in ulcerative colitis and anti-inflammatory signals in Crohn's disease. Furthermore, it was shown that SHP647 does not affect the number and composition of cells in cerebrospinal fluid, suggesting that the compound is not affecting immune surveillance in the central nervous system. In addition, both alicaforsen and SHP647 are promising compounds based on the clear safety profile observed so far.